2019
DOI: 10.1371/journal.pone.0217516
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction offers the most effective marker assisted breeding approach for ability to prevent arsenic accumulation in rice grains

Abstract: The high concentration of arsenic ( As ) in rice grains, in a large proportion of the rice growing areas, is a critical issue. This study explores the feasibility of conventional (QTL-based) marker-assisted selection and genomic selection to improve the ability of rice to prevent As uptake and accumulation in the edible grains. A japonica diversity panel (RP) of 228 accessions phenotyped for As concentration in the flag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…We are aware that the optimized scheme we suggest, based on random sampling of the training set, genome-wide markers considered as random effects, and random allocation of genotypes to sparse testing could be improved further still by considering other criteria known to increase the performance of GP. It remains to be seen whether PA can be improved by optimized assembly of the training set as performed in various studies ( Rincent et al 2012 , 2017 ; Bustos-Korts et al 2016 ; Akdemir and Isidro-Sánchez 2019; Mangin et al 2019 ), by inclusion of particular weights for some specific loci ( Spindel et al 2016 ; Bhandari et al 2019 ; Frouin et al 2019 ) or by use of an efficient method to proceed to sparse testing in the context of GxE models ( Ahmadi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that the optimized scheme we suggest, based on random sampling of the training set, genome-wide markers considered as random effects, and random allocation of genotypes to sparse testing could be improved further still by considering other criteria known to increase the performance of GP. It remains to be seen whether PA can be improved by optimized assembly of the training set as performed in various studies ( Rincent et al 2012 , 2017 ; Bustos-Korts et al 2016 ; Akdemir and Isidro-Sánchez 2019; Mangin et al 2019 ), by inclusion of particular weights for some specific loci ( Spindel et al 2016 ; Bhandari et al 2019 ; Frouin et al 2019 ) or by use of an efficient method to proceed to sparse testing in the context of GxE models ( Ahmadi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results have immediate implications for rice breeding programs in West Africa. The abundance of small-effect loci, predominantly from the indica subpopulation, contributing to HIA stress tolerance suggests that a recurrent selection program focusing on an expanded indica genepool could be used in combination with genomic selection (GS) to increase the efficiency of the breeding process ( Begum et al, 2015 ; Grenier et al, 2015 ; Cobb et al, 2019 ; Frouin et al, 2019 ). The accuracy of GS models can often be improved by differentially weighting SNPs known to be associated with favorable GWA-QTL alleles, such as those reported here ( Spindel et al, 2016 ; Bhandari et al, 2019 ; Li et al, 2019 ; Liu et al, 2019 ; Rice and Lipka, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, GWAS further identified loci, including new genes associated with Cd accumulation and tolerance (Arabidopsis: Chao et al, 2012;Aegilops tauschii: Qin et al, 2015;barley: Wu et al, 2015;rapeseed: Chen et al, 2018;rice: Zhao et al, 2018a, maize: Zhao et al, 2018b. Similarly, GWAS for As accumulation was conducted, by which some associated genes were identified that were functionally distinct from the previously characterized genes (Chao et al, 2014;Zhao et al, 2018c;Frouin et al, 2019). The information of loci revealed by GWAS can be exploited for improving the efficiency of breeding of not only significantly low accumulation in the edible parts but also for enhancing the tolerance for toxic minerals, in addition to using major responsible genes and the orthologue genes in various plants Plant-derived food provides essential micronutrients for human health.…”
Section: Gwas For Mineral Contentmentioning
confidence: 99%